THE USE OF SLANG AMONG AMERICAN YOUTHS AS RELATED TO THE RISE OF HIP HOP CULTURE: A SOCIOLINGUISTICS ANALYSIS - Niken Fatma Putri; Fauzia Fauzia (UAD TEFL International Conference)
This article entitled “The Use of Slang among American Youths as Related to The rise of Hip Hop Culture: A Sociolinguistics Analysis”. This research focuses on the types of slang commonly used by American youths and the influence of hip hop on slang use among American youths.This research belongs to descriptive qualitative research as a method.  The subject of this research is rap song lyrics, utterances in slang in America YouTube video and Ellen Show: On Fleek Episode as well as the Urban Dictionary slangs. Then, the objects of this research are the use of slang. The researcher collected the data through the utterances in the rap song lyrics,  movie and video, and also slangs in Urban Dictionary.The results of this analysis show that the type of slang used among American youths are divided into two types. They are based on use and word formation. Meanwhile the use of slang among American youths is related to the rise of hip hop culture influence which brought by some of rap song. The slang contained in rap song lyrics are spread easily by the massive consumption of social media and enlighten highly by the report of conventional media.